Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1007/s10826-020-01885-0
|View full text |Cite
|
Sign up to set email alerts
|

Examining Longitudinal Relations Between Mothers’ and Fathers’ Parenting Stress, Parenting Behaviors, and Adolescents’ Behavior Problems

Abstract: Parenting stress of mothers has frequently been linked to negative child outcomes. According to Abidin’s stress model, this relationship may be explained by dysfunctional parenting behaviors. In this study, we scrutinized the effects of both mothers and fathers in the pathway from parenting stress through parenting behaviors to subsequent adolescent behavior problems. We expected the association between parenting stress and adolescent behavior problems to be partially mediated by maternal and paternal parentin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 58 publications
0
16
0
1
Order By: Relevance
“…A strength of the present study is that we oversampled for families with lower income, higher stress, and higher child maltreatment risk, factors that can pose challenges for parenting behavior (de Maat et al, 2021; Keim et al, 2011) and child self-regulation (Lunkenheimer, Ram, et al, 2017) and have been shown to alter parent–child coregulation patterns (Diercks et al, 2020). Thus, findings suggest EC is promotive of parent–child behavioral concordance in at-risk community populations, adding to a body of literature on the importance of child self-regulation as a key mechanism of adaptation in the face of risk (Tiberio et al, 2016), as well as specific studies on its role in relation to harsh parenting (Dumas et al, 2001; Lunkenheimer, Ram, et al, 2017; Patterson, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…A strength of the present study is that we oversampled for families with lower income, higher stress, and higher child maltreatment risk, factors that can pose challenges for parenting behavior (de Maat et al, 2021; Keim et al, 2011) and child self-regulation (Lunkenheimer, Ram, et al, 2017) and have been shown to alter parent–child coregulation patterns (Diercks et al, 2020). Thus, findings suggest EC is promotive of parent–child behavioral concordance in at-risk community populations, adding to a body of literature on the importance of child self-regulation as a key mechanism of adaptation in the face of risk (Tiberio et al, 2016), as well as specific studies on its role in relation to harsh parenting (Dumas et al, 2001; Lunkenheimer, Ram, et al, 2017; Patterson, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Stres pengasuhan menurut Berry dan Jones (1995) merupakan pengalaman negatif orang tua dalam memenuhi tuntutan pengasuhan. Konsep yang serupa diajukan oleh de Maat et al (2021), stres pengasuhan didefinisikan sebagai perasaan negatif terhadap diri sendiri dan anak akibat tanggung jawab pengasuhan yang dirasa membebani. Bentuk pengalaman negatif yang dialami dapat berupa kehilangan sumber daya seperti waktu, energi, selfesteem, kendali, kebahagiaan, ataupun kasih sayang saat mengasuh anak (Zelman & Ferro, 2018).…”
Section: Pengasuhanunclassified
“…Parenting stress, typically defined as individuals' perception of the difficulties and feelings in not being able to meet the demands of being a parent (Abidin, 1992;Crnic and Low, 2002;Deater-Deckard, 2008), has received much attention during the past decades. The available evidence suggests that excessive parenting stress reduces the use of positive parenting behaviors, such as warmth and responsiveness (Fonseca et al, 2020;Ward and Lee, 2020;de Maat et al, 2021), and is associated with higher levels of negative parenting behaviors, for instance, over-reactivity, and permissiveness (Fonseca et al, 2020;Mak et al, 2020;de Maat et al, 2021), regardless of whether children have developmental disabilities (Ueda et al, 2020). There is also evidence to suggest that such stress-related effects are enduring in nature and affect children's social-emotional, behavioral, and cognitive development (Bosquet Enlow et al, 2019;Cherry et al, 2019;Mak et al, 2020;Ward and Lee, 2020;Kochanova et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…There is also evidence to suggest that such stress-related effects are enduring in nature and affect children's social-emotional, behavioral, and cognitive development (Bosquet Enlow et al, 2019;Cherry et al, 2019;Mak et al, 2020;Ward and Lee, 2020;Kochanova et al, 2021). Although the majority of studies about parenting stress were conducted in western and Anglo-European countries (Touchèque et al, 2016;Rivas et al, 2020;de Maat et al, 2021), an increasing number of studies are conducted in Asia (Ilias et al, 2018;Lau and Power, 2020;Mak et al, 2020).…”
Section: Introductionmentioning
confidence: 99%